Influencia del programa "WORDS BY SONGS" en el incremento del vocabulario del idioma inglés en estudiantes del 4to grado "A" y "B" del nivel primaria de la l.E. "Miguel Chuquisengo Ramírez" Tarapoto - 2014 - Romero Tejada, Sindy Marisela (2015)
The following research deals with a methodological proposal in the teaching of vocabulary through the use of songs in English from the view of the musical expression and the English language. This research has an interdisciplinary approach between music and language in order to achieve a meaningful learning for the student, with the attempt to increase the English vocabulary of these students. The proposal is based on the importance of singing as a motivating activity for the students. Besides, the Psychomotricity Stage makes an important contribution for the success of this investigation. Students express themselves with their body and at the same time they sing, this improves the learning process. The song as a fusion of music and language is the ideal way of developing the expression and communication among people. lt is an essential element of the daily musical behavior, therefore it is necessary for the students to know many songs so these can give them expressive variety and raises their interest, and it becomes one of the most meaningful learning. For making possible this goal, we have gathered information from an experimental group of students in the 4th Grade "B" a sample of ten (10) of the l.E Miguel Chuquisengo Ramirez - Tarapoto 2014, we have applied a pre-test based on questions related to the contents we develop during the program "WORDS BY SONGS" which are based on the simultaneous development of 6 other workshops which their main goal is to improve the vocabulary in English. By the end of the 6 learning activities, we have applied a post-test to be contrasted with the first pre-test and carry out the tabulation, description, and analysis corresponding to the data. The respective comparison of scores gave as result the increment on average in scores of 07 to 16 just as the chart Nº 11 shows. This graphic at the same time shows that students of the 4th grade "B" at l.E Miguel Chuquisengo Ramirez - Tarapoto 2014 have considerably improved the vocabulary.